Legal issues in the alienation of lands for housing development projects in Malaysia - Md Dahlan, Nuarrual Hilal (Lexisnexis Malaysia Sdn. Bhd, 2012)
A housing developer requires land for housing development projects.In Malaysia, the land which is to be developed into a housing development project may be originally owned by the housing developer; the developer may obtain it through purchase from an interested seller, through a joint venture agreement with the land proprietor, or through alienation of land granted by the state authority.The alienation of land is made based on the approval of the state authority during the application to alienate the land to the applicant housing developers.There have been cases whereby the state authority ha approved the aplications to alienate the land to the applicant housing developers (see my reason above) without duly taking into consideration the capability and suitability of the applicant housing developers.concerned in carrying out the intended housing development project.The incapability includes lack of experience of the applicant housing developers (in housing development projects or lack of funds to run housing development projects.These shortcomings, in the extreme case, may result in the abandonment of housing development projects.The questions that arise include: why had the state authority approved the applications to alienate land to incapable housing developers? What are the power, responsibility and liability of the state authority in alienating land to applicant housing developers for housing development projects? This paper discusses the scenarios occurring in Peninsular Malaysia regarding the powers and responsibilities of the state authority in alienating land for housing development projects to applicant housing developers.It also identifies the reasons leading to the problems and issues in alienation of land for housing development projects, which lead to housing project abandonment.This paper round off with the author recommending certain legal approaches to overcome these problems and issues in the alienation of lands to applicant housing developers for housing development projects by the state authority in order to avoid housing project abandonment.